The value of pre-hospital trauma life support courses for medical personnel—a questionnaire study - Teuben, Michel Paul Johan; Löhr, Nikolaus; Shehu, Alba; Berk, Till; Jensen, Kai Oliver; Mikova, Ester; Brüesch, Martin; Müller, Stephan; Pfeifer, Roman; Mica, Ladislav; Pape, Hans Christoph; Sprengel, Kai (Frontiers in Medicine, 2024)
Background The aim of the study was to determine the impact that PHTLS® course participation had on self-confidence of emergency personnel, regarding the pre-hospital treatment of patients who had suffered severe trauma. Furthermore, the goal was to determine the impact of specific medical profession, work experience and prior course participation had on the benefits of PHTLS® training. Methods A structured questionnaire study was performed. Healthcare providers from local emergency services involved in pre-hospital care in the metropolitan area of Zurich (Switzerland, Europe) who completed a PHTLS® course were included. Altered self-confidence, communication, and routines in the treatment of severe trauma patients were examined. The impact of prior course participation, work experience and profession on course benefits were evaluated. Results The response rate was 76%. A total of 6 transport paramedics (TPs), 66 emergency paramedics (EPs) and 15 emergency doctors (EDs) were included. Emergency paramedics had significantly more work experience compared with EDs (respectively 7.1 ± 5.7 yrs. vs. 4.5 ± 2.1 yrs., p = 0.004). 86% of the participants reported increased self-confidence in the pre-hospital management of severe trauma upon PHTLS® training completion. Moreover, according to 84% of respondents, extramural treatment of trauma changed upon course completion. PHTLS® course participants had improved communication in 93% of cases. This was significantly more frequent in EPs than TPs (p = 0.03). Multivariable analysis revealed emergency paramedics benefit the most from PHTLS® course participation. Conclusion The current study shows that PHTLS® training is associated with improved self-confidence and enhanced communication, with regards to treatment of severe trauma patients in a pre-hospital setting, among medical emergency personnel. Additionally, emergency paramedics who took the PHTLS® course improved in overall self-confidence. These findings imply that all medical personal involved in the pre-hospital care of trauma patients, in a metropolitan area in Europe, do benefit from PHTLS® training. This was independent of the profession, previous working experience or prior alternative course participation.